Curricular Enrichment Propositions in Common Class: Renzulli’s Triadic Enrichment Model - Bergamin, Aletéia Cristina; Fiorot Junior, José Angelo; Rondini, Carina Alexandra (Revista Electrónica Educare, 2025)
Introduction. Students with high abilities or giftedness have the right, under current legislation, to curricular enrichment as a pedagogical strategy. In addition to providing this target audience with special education by considering their interests and abilities, offering enrichment in the general classroom benefits all students. Purpose. This study analyzes whether the knowledge acquired in courses on high abilities and giftedness by undergraduate and graduate students facilitates the development of curricular enrichment programs for Basic Education students. Methodology. This is a descriptive study that employed document analysis of academic works produced by undergraduate Pedagogy students and graduate Psychology students, as part of the requirements of disciplines on high abilities and giftedness, both of which were elective courses offered at different campuses of a public university within the State of São Paulo. Results. A selection of these works was analyzed within the theoretical framework of the Triadic Enrichment Model, assessing successful applications and proposing refinements for identified inconsistencies. Conclusion. The final reflections emphasize the importance of initial and continuing education on this topic, such as those proposed for actions to be undertaken in the professional field to become assertive.